Intensity dependence in the dissociation branching ratio of ND+ using intense femtosecond laser pulses - McKenna, J.; Sayler, A. M.; Gaire, B.; Johnson, Nora G.; Parke, E.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, I. (My University, 2008)
We investigate the dependence of the dissociation branching ratio of ND+ on intensity in the strong-field regime. ND+, unexplored previously using an intense laser, offers an interesting, alternating sequence of dissociation limits to N++D and N+D+ separated by less than the photon energy at 795 nm wavelength. By exposing an ND+ beam to a 40 fs Ti:sapphire laser pulse and measuring the ion fragments in coincidence with the neutral fragments, we find that the branching ratio of the final dissociation channel depends strongly on intensity in the range 2×1013–3×1015 W/cm2. Furthermore, we use measurements of the kinetic energy release and angular distributions for these channels to identify their most probable dissociation pathways.